Thermal Design and Experimental Verification of High-Frequency Auxiliary Converter for Metro Vehicle - YI Tao; LIU Qing; GENG Zhidong; ZHAO Qingliang; ZHOU Qiaolian; DENG Qi (机车电传动)
With the switching frequency of auxiliary converters continues to increase, reasonable thermal design is a prerequisite for ensuring the normal operation of auxiliary converters. The thermal design of products was studied according to the high-frequency auxiliary converter for metro vehicle. The power loss of key components was calculated by PLECS, and the cooling system which consisted of multi-duct was designed. The temperature rise of key components was analyzed by establishing the thermal simulation model of the system using Icepak; finally, temperature rise test of prototype was done. Through comparative analyses, the results of temperature rise simulation were in good agreement with test results, which verified the validity of the simulation analysis, and the temperature rise of the key modules was less than 45 K, which met the heat dissipation requirements of the system. The paper provided methods for the preliminary design and optimization of the high frequency auxiliary converter.